RETRACTED: The Role of Janus Kinase/STAT3 Pathway in Hematologic Malignancies With an Emphasis on Epigenetics - Zeinalzadeh, Elham; Valerievich Yumashev, Alexey; Rahman, Heshu Sulaiman; Marofi, Faroogh; Shomali, Navid; Kafil, Hossein Samadi; Solali, Saeed; Sajjadi-Dokht, Mehdi; Vakili-Samiani, Sajjad; Jarahian, Mostafa; Hagh, Majid Farshdousti (Frontiers in Genetics, 2021)
ABSTRACT The Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway has been known to be involved in cell growth, cellular differentiation processes development, immune cell survival, and hematopoietic system development. As an important member of the STAT family, STAT3 participates as a major regulator of cellular development and differentiation-associated genes. Prolonged and persistent STAT3 activation has been reported to be associated with tumor cell survival, proliferation, and invasion. Therefore, the JAK-STAT pathway can be a potential target for drug development to treat human cancers, e.g., hematological malignancies. Although STAT3 upregulation has been reported in hematopoietic cancers, protein-level STAT3 mutations have also been reported in invasive leukemias/lymphomas. The principal role of STAT3 in tumor cell growth clarifies the importance of approaches that downregulate this molecule. Epigenetic modifications are a major regulatory mechanism controlling the activity and function of STAT3. So far, several compounds have been developed to target epigenetic regulatory enzymes in blood malignancies. Here, we discuss the current knowledge about STAT3 abnormalities and carcinogenic functions in hematopoietic cancers, novel STAT3 inhibitors, the role of epigenetic mechanisms in STAT3 regulation, and targeted therapies, by focusing on STAT3-related epigenetic modifications.